A giant magnetocaloric effect with a tunable temperature transition close to room temperature in Na-deficient La0.8Na0.2−x□xMnO3 manganites. Issue 28 (28th July 2015) - Wali, M.; Skini, R.; Khlifi, M.; Dhahri, E.; Hlil, E. K.
<x xml:space="preserve">Abstract</x> A giant magnetocaloric effect induced by sodium-deficiency in a La0.8Na0.2−x□xMnO3 (0.00 ≤ x ≤ 0.15) polycrystalline sample is reported in the present research work.